HIV testing uptake and retention in care of HIV‐infected pregnant and breastfeeding women initiated on 'Option B+' in rural Zimbabwe. Issue 2 (8th December 2015) - Dzangare, Janet; Takarinda, Kudakwashe C.; Harries, Anthony D.; Tayler‐Smith, Katie; Mhangara, Mutsa; Apollo, Tsitsi Mutasa; Mushavi, Angela; Chimwaza, Anesu; Sithole, Ngwarai; Magure, Tapiwa; Mpofu, Amon; Dube, Freeman; et al.
Abstract: Objectives: Zimbabwe has started to scale up Option B+ for the prevention of mother‐to‐child transmission of HIV, but there is little published information about uptake or retention in care. This study determined the number and proportion of pregnant and lactating women in rural districts diagnosed with HIV infection and started on Option B+ along with six‐month antiretroviral treatment (ART) outcomes. Methods: This was a retrospective record review of women presenting to antenatal care or maternal and child health services at 34 health facilities in Chikomba and Gutu rural districts, Zimbabwe, between January and March 2014. Results: A total of 2728 women presented to care of whom 2598 were eligible for HIV testing: 76% presented to antenatal care, 20% during labour and delivery and 4% while breastfeeding. Of 2097 (81%) HIV‐tested women, 7% were HIV positive. Lower HIV testing uptake was found with increasing parity, late presentation to antenatal care, health centre attendance and in women tested during labour. Ninety‐one per cent of the HIV‐positive women were started on Option B+. Six‐month ART retention in care, including transfers, was 83%. Loss to follow‐up was the main cause of attrition. Increasing age and gravida status ≥2 were associated with higher six‐month attrition. Conclusion: The uptake of HIV testing and Option B+ is high in women attending antenatal and post‐natal clinics in rural Zimbabwe, suggesting that the strategy is feasible for national scale‐up in the country.